Chemokines and Chemokine Receptors: Orchestrating Tumor Metastasization - Elisabetta Marcuzzi (International Journal of Molecular Sciences, 2018)
Metastasis still represents the primary cause of cancer morbidity and mortality worldwide. Chemokine signalling contributes to the overall process of cancer growth and metastasis, and their expression in both primary tumors and metastatic lesions correlate with prognosis. Chemokines promote tumor metastasization by directly supporting cancer cell survival and invasion, angiogenesis, and by indirectly shaping the pre-metastatic niches and antitumor immunity. Here, we will focus on the relevant chemokine/chemokine receptor axes that have been described to drive the metastatic process. We elaborate on their role in the regulation of tumor angiogenesis and immune cell recruitment at both the primary tumor lesions and the pre-metastatic foci. Furthermore, we also discuss the advantages and limits of current pharmacological strategies developed to target chemokine networks for cancer therapy.